Novel mechanism of the negative thermal expansion of doped fullerite C₆₀ - Strzhemechny, M.A.; Legchenkova, I.V. (Физика низких температур, 2010)
A model for an atomic impurity in an octahedral void of fullerite C₆₀ is suggested. The problem is solved in the spherical oscillator approximation, which is appropriate for the larger rare gas atoms. It is shown that such impurities can contribute to the negative thermal expansions at low temperatures and produce a Schottky-like maximum at higher temperatures.